SOA Based Universal Application Integration Framework - Beg, Javed; Mehfuz, Shabana; Doja, M. N. (Gyan Management Journal, 2008)
In current enterprise wide business scenarios, there is a strong requirement for software applications to work in an integrated and synchronized manner. Application Integration building methodology always_using the Target application specific technologies could prove to be a cumbersomeapproach when the number of targets scale to a large level. The complexity would lead to extra cost fodevelopment and maintenance cycles. To tackle this issue for an integration scenario between a single Master Application and similar kind of Target applications ( compatible with same Data Transport and Format mechanisms), this paper presents a design approach guideline, based on Service Oriented Architecture (SOA) principles. The proposed architecture could not only be used for flexibly plugging-in Transport and Format providers but also for including Data Cleansing components in the integration layer.